Women Entrepreneurs and Stand-up India Scheme in Punjab: A critical review - Kaur, Lakhwinder; Arora, Jyoti (Gyan Management Journal, 2022)
The study of financial inclusion has always been important for our country’s  government and central bank, and it has now become even more important  in light of the impact of a recession-like situation prevailing in the country.  The need of the hour is to have a deeply embedded financial system that  not only aids in the fight against recession but also ensures the successful  operation of the nation’s financial system which is heavily reliant on the  active participation of every sector of the economy. To achieve the aim of  financial inclusion, the Stand-up India scheme for both women and ST/ SC entrepreneurs was launched by the government of India. The issue of  the government’s responsibility for ensuring that women entrepreneurs  have access to an entrepreneurial environment is of great importance. To  make this scheme truly beneficial for women entrepreneurs, it should be  the primary focus area for the government. This paper aims to analyze the  Stand-Up India scheme from a gender perspective. The study aims to assess  the Stand-Up India scheme in detail with reference to the benefits that the  women entrepreneurs will get from it and to study the impact of the stand up scheme on the upliftment of women beneficiaries in Punjab. For this  study, both primary and secondary sources of information have been used.
Keywords: Financial Inclusion; women entrepreneurs; entrepreneurial environment